Focalization and Word Order in Old Italo-Romance - Silvio Cruschina (Universitat Autònoma de Barcelona, 2011)
This paper sets out a comparison between modern and old Italo-Romance varieties with the aim of understanding the mechanisms that characterize the syntactic operations associated with the information structure of the sentence, as well as identifying their triggering factors. In particular, this study concentrates on the process of focalization and the movement operations related to it: constituent fronting and verb movement. In light of the synchronic variation found in modern Italo-Romance varieties, it is argued that most of the properties generally attributed to a V2 system found in the languages in question are instead associated with discourse-related features and functional projections. A distinction between a higher, left peripheral FocP and a lower, clause-internal FocP provides the basis for an account of both synchronic and diachronic variation, the analysis of which rests on a correlation between word order changes in diachrony, discourse-related features, and functional projections.